2016
DOI: 10.1186/s12903-016-0194-z
|View full text |Cite
|
Sign up to set email alerts
|

Cleansing effect of acidic L-arginine on human oral biofilm

Abstract: BackgroundDental plaque formed on tooth surfaces is a complex ecosystem composed of diverse oral bacteria and salivary components. Accumulation of dental plaque is a risk factor for dental caries and periodontal diseases. L-arginine has been reported to decrease the risk for dental caries by elevating plaque pH through the activity of arginine deiminase in oral bacteria. Here we evaluated the potential of L-arginine to remove established oral biofilms.MethodsBiofilms were formed using human saliva mixed with B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 45 publications
0
16
0
1
Order By: Relevance
“…Clinical investigations containing Arg dentifrices or mouth rinses showed a protective effect against development of dental caries in young subjects. In addition, Arg and fluoride synergistically suppressed Streptococcus mutans growth and biofilm formation . A dentifrice containing 1.5% Arg, a calcium compound, and fluoride (parts per million; ppm) has been developed and authenticated for use.…”
Section: Role Of Arginine In Oral Healthmentioning
confidence: 99%
See 3 more Smart Citations
“…Clinical investigations containing Arg dentifrices or mouth rinses showed a protective effect against development of dental caries in young subjects. In addition, Arg and fluoride synergistically suppressed Streptococcus mutans growth and biofilm formation . A dentifrice containing 1.5% Arg, a calcium compound, and fluoride (parts per million; ppm) has been developed and authenticated for use.…”
Section: Role Of Arginine In Oral Healthmentioning
confidence: 99%
“…In addition, it has been reported to reduce the pathogenicity of herpes simplex and influenza viruses, probably due to compromised function of proteins in the envelope. 31 The functions of Arg has revealed that it is in involved in the regulation of immune cells in cancer, inflammation, infections, etc. 26,[32][33][34][35][36][37][38][39][40] Arg is synthesized from glutamine, glutamate, and proline via the intestinal-renal axis in humans and other mammals (such as pigs, sheep, and rats).…”
Section: Windmueller and Spaeth Reported That The Small Intestimentioning
confidence: 99%
See 2 more Smart Citations
“…However, at high concentrations (≥50 m m ), arginine can disrupt coaggregation between S. gordonii and F. nucleatum by inhibiting the F. nucleatum adhesin RadD . High concentrations of arginine also disrupt multispecies oral microbial biofilms or S. gordonii monospecies biofilms …”
Section: Introductionmentioning
confidence: 99%